2020
DOI: 10.12965/jer.2040030.015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lower limb muscle asymmetry during the sit-to-stand task and spatiotemporal gait asymmetry in subjects with stroke

Abstract: The purpose of this study was to investigate the relationship between the both lower limb muscle asymmetry during sit-to-stand (STS) and spatiotemporal gait asymmetry in subjects with stroke. Twenty-nine patients were included in this study, lower limb muscle (rectus femoris, tibialis anterior, gastrocnemius) asymmetry during STS, five times sit-tostand (FTSTS) and spatiotemporal (speed, step length, step time, swing time, stance time, single support time) gait asymmetry were measured. According to the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Previous studies show significant negative correlation between sit to stand and gait velocity [31] and there is literature stating that sit to stand can be considered a valid measure to predict community ambulation of stroke patients [32]. Both of these align with the findings of our study showing a relationship between sit to stand functional ambulation in stroke patients and infer that training one aspect may show effect on the ambulatory capacity of an individual affected by stroke.…”
Section: Correlation Analysis Between Sit To Stand and Functionalsupporting
confidence: 91%
“…Previous studies show significant negative correlation between sit to stand and gait velocity [31] and there is literature stating that sit to stand can be considered a valid measure to predict community ambulation of stroke patients [32]. Both of these align with the findings of our study showing a relationship between sit to stand functional ambulation in stroke patients and infer that training one aspect may show effect on the ambulatory capacity of an individual affected by stroke.…”
Section: Correlation Analysis Between Sit To Stand and Functionalsupporting
confidence: 91%
“…The STS task evaluates the MF of the lower limbs [ 18 ] and is related to a decrease in gait speed [ 32 ]. Our study revealed that MF was positively associated with walking speed at FWS and stride time at SWS and negatively associated with the CV of step time at SWS and CV of single support phase at PWS.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling of the EMG signal was 1,000 Hz, the frequency bandwidth was 20 to 1,000 Hz, and a 50 Hz notch filter was used. EMG data for muscle activity were processed using root mean square (RMS) and the values were normalized to referenced voluntary contraction (RVC) ( Ju, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of the dominant leg was measured from the time the buttocks were lifted off the chair until the knees were straightened ( Lee and Yoo, 2017 ). RVC measured the activity of the rectus abdominal muscle (RA), quadriceps, and tibialis anterior on the dominant side when maintaining a quiet standing position for 5 sec ( Ju, 2020 ), and was measured for 3 sec excluding the first and last 1 sec. Each measurement was performed 3 times, and the average value was used.…”
Section: Methodsmentioning
confidence: 99%